Prevalence of Odontogenic Tumors in Udaipur Region -An Institutional Retrospective Analysis of 56 Cases - Satish Bhosale; Priyadarshini Kerur; Rohit Kumar; Pradeep Vishnoi; Rahul Chaplot; Gargi Nimbulkar (Journal of Pharmacy and Bioallied Sciences)
Introduction: Odontogenic tumors are lesions that originate from the tooth-producing tissues or their remnants that remain entrapped either within the jawbones or into the adjacent soft tissues. They comprise a range of disorders of growth, from malignant and benign neoplasms, to malformations of dental tissues of self-limited growth. Aim: To do a retrospective analysis of 56 cases of odontogenic tumors in oral cavity over a period of 5 years. Materials and Methods: Institutional histopathology registry was scrutinized to gather data of cases of odontogenic tumors over a period of 5 years (2020-2024). The information of all the cases was thoroughly reviewed, analyzed, and tabulated. Results: A total of 56 cases of odontogenic tumors were found. Males were most commonly affected than females (M > F). The most common site was posterior mandible (molar-ramus) region. We found 19 cases of solid multicystic ameloblastoma (SMA), 22 cases of unicystic ameloblastoma, 5 cases of KCOT, 3 cases each of desmoplastic ameloblastoma and AOT, and 2 each of peripheral ameloblastoma and ameloblastic carcinoma. Conclusion: Ameloblastoma was the commonest odontogenic tumor with unicystic variant being 39.28% followed by SMA (33.92%), KCOT (8.92%), AOT (5.35%), and desmoplastic variant (5.35%).